Implementasi Bantuan Pembangunan Program Air dan Sanitasi USAID IUWASH PLUS di Indonesia Tahun 2021 - Andi Muhammad Farid Ramadhan; M. Syaprin Zahidi (Jayapangus Press, 2023)
This study aims to analyze the implementation of the USAID IUWASH PLUS 2021 water and sanitation program development assistance in Indonesia. Due to the clean water and sanitation problems in Indonesia, the United States government, through USAID, distributes aid in the form of grants. This research applies a qualitative research method with a case study approach. The collected data were analyzed using the concepts of foreign aid and aid effectiveness. The results of this study found that the authors linked the principles contained in the Paris Declaration such as the principle of ownership, the principle of local harmony, the principle of harmonization, the principle of management and the principle of shared responsibility. The USAID IUWASH PLUS program is effective in improving water and sanitation services in Indonesia, referring to the results published by USAID in the February 2022 Final Report.